THE INFLUENCE OF LIBRARY USE ON STUDENTS' LITERACY - Febrianti, Wina; Dalimunthe, Muhammad; Naldo, Jufri (Academic Solution Publisher, 2023)
This study aims to find out how students use information services in the library of SMA Negeri 1 Pematang Bandar, the information literacy skills of SMA Negeri 1 Pematang Bandar, and the effect of using the library on students' literacy in SMA Negeri 1 Pematang Bandar. This research uses a questionnaire research method or questionnaire as a means of collecting data obtained by respondents. The population of this study were all students of SMA Negeri 1 Pematang Bandar starting from class X-XII, namely 407 students with a total sample of 80 students which was determined by the slovin formula. The sampling technique used to determine the sample is probability sampling The conclusion of this study is that students of SMA Negeri 1 Pematang Bandar have sufficiently utilized the library by having the desire to visit, then some teachers use the library when carrying out learning activities, and utilize the facilities in the library by borrowing books, information literacy skills of high school students Negeri 1 Pematang Bandar can be classified as good by looking at its average value of 27.60, and based on the results of f count 23.021 with a significance level of 0.000 <0.05, the regression model can be used to predict variable X or in other words there is a significant effect Utilization of Libraries (X) on Information Literacy (Y).